Hunter-gatherer color naming provides new insight into the evolution of color terms - Lindsey, Delwin T. (Curr Biol, 2015)
Most people name the myriad colors in the environment using between two and about a dozen color terms [1], with great variation within and between languages [2]. Investigators generally agree that color lexicons evolve from fewer terms to more terms, as technology advances and color communication becomes increasingly important [3]. However, little is understood about the color naming systems at the least technologically-advanced end of the continuum. The Hadza people of Tanzania are nomadic hunter-gatherers who live a subsistence lifestyle that was common before the advent of agriculture (see SM-I, [4]), suggesting that the Hadzane language should be at an early stage of color lexicon evolution. When Hadza, Somali, and U.S. informants named 23 color samples, Hadza informants named only the black, white and red samples with perfect consensus. Otherwise, they used low-consensus terms, or responded “don’t know”. However, even low-consensus color terms grouped test colors into lexical categories that aligned with those found in other world languages [5]. Furthermore, information-theoretic analysis showed that color communication efficiency within the Hadza, Somali, and U.S. language communities falls on the same continuum as other world languages. Thus, the structure of color categories is in place in Hadzane, even though words for many of the categories are not in general use. These results suggest that even very simple color lexicons include precursors of many color categories, but that these categories are initially represented in a diverse and distributed fashion.